Psychiatric disorders causing trichotylomania (Research, Society and Development, 2022)
Trichotillomania is a disorder marked by the compulsive act of removing hair from one's own body. Although little studied over the last decades, studies demonstrate an association of this condition with other psychiatric disorders. With this in mind, the present study seeks to elucidate the main psychiatric disorders that cause trichotillomania. This is a systematic literature review, in which articles were searched in the Google Escolar, Scientific Electronic Library Online and Pubmed databases using the following terms and descriptors: “trichotillomania”, “Rapunzel syndrome” or “trichobezoar” and the Boolean operator AND. PRISMA guidelines were also followed throughout the selection process. The prevalence of psychiatric disorders associated with trichotillomania ranged from 78.8% to 79% among the selected studies. The most cited disorders by the authors were: obsessive compulsive disorder, major depressive disorder, generalized anxiety disorder, social phobia, specific phobia, excoriation disorder, pathological nail biting, TICS disorder, alcohol dependence and dysthymic disorder. All authors demonstrated a high prevalence of psychiatric disorders associated with the occurrence of trichotillomania.